2013
DOI: 10.3109/10715762.2013.857019
|View full text |Cite
|
Sign up to set email alerts
|

S-allyl cysteine protects against MPTP-induced striatal and nigral oxidative neurotoxicity in mice: Participation of Nrf2

Abstract: The neuroprotective properties of S-allyl cysteine (SAC) have been demonstrated in different neurotoxic paradigms, and it may be partially attributable to its antioxidant and anti-inflammatory profile. Recently, SAC has also been shown to induce neuroprotection in the rat striatum in a toxic model induced by 6-hydroxydopamine in rats through a concerted antioxidant response involving Nrf2 transcription factor nuclear transactivation and Phase 2 enzymes' upregulation. In this work, we investigated whether the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Here, the striatal Nrf-2 expression was not modified by MTZ exposure. We did not expect this result since several studies, mainly related to Parkinson disease models, have demonstrated that this transcription factor in the striatum and/or dopaminergic neurons can be modulated by different drugs, including methamphetamine, 6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridinium (MPTP) [81,82]. The results obtained here indicate that the pattern of gene expression in response to hypothyroidism is complex and depends on the brain region considered.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the striatal Nrf-2 expression was not modified by MTZ exposure. We did not expect this result since several studies, mainly related to Parkinson disease models, have demonstrated that this transcription factor in the striatum and/or dopaminergic neurons can be modulated by different drugs, including methamphetamine, 6-hydroxydopamine and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridinium (MPTP) [81,82]. The results obtained here indicate that the pattern of gene expression in response to hypothyroidism is complex and depends on the brain region considered.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, contrary to what would be expected in a stress protocol, the elevated-plus maze and forced-swimming tests revealed that animals subjected to acute restraint are less depressed, exhibit less anxiety, and are more prompt to show their survival instinct by struggling and socializing [45,47], therefore supporting our suggestion that under the experimental conditions employed in this study, acute stress represents a phase in which individuals are still capable to display "fighting-back" adaptive responses to counteract adverse situations. Noteworthy, the use of SAC as pretreatment in stressed rats ameliorated and/or prevented all the behavioral alterations explored herein, thereby supporting the involvement of oxidative stress in acute restraint stress and emphasizing the many beneficial properties exerted by this antioxidant in in vivo toxic models [13,14,38,39]. Nonetheless, although brief and transitory, the behavioral changes Stress is known to stimulate the activation of numerous pathways leading to altered levels of hormones, neurotransmitters, oxidants, and several other substances.…”
Section: Accepted Manuscriptmentioning
confidence: 84%
“…In light of the preventive effects exerted by SAC in this study, we suggest that most of its actions could correspond to its properties as free radical scavenger [7,21,30], although in addition to its direct scavenging activity, SAC has been shown to exert protection in the model of hemi-parkinsonism induced by MPTP through the stimulation of the Nrf2 pathway [14]. This transcription factor is currently in charge of signaling for the synthesis of antioxidant defenses (phase 2 enzymes) to counteract toxic insults and to preserve the redox homeostasis [9].…”
Section: Accepted Manuscriptmentioning
confidence: 90%
See 2 more Smart Citations